Biochar; an effective factor in improving phytoremediation of metal(iod)s in polluted sites - Boorboori, Mohammad Reza; Lackóová, Lenka (Frontiers in Environmental Science, 2023)
Phytoremediation is one of the cheapest and most widely used technologies for stabilizing and extracting pollutants from contaminated sites. Recently, a variety of solutions, such as the use of different elements, compost, nanoparticles, microorganisms, etc. have been explored for improving and accelerating the phytoremediation process. Biochar has also gained attention for its affordability, abundance, ability to improve soil structure and plant morpho-physiology and biochemistry, lack of environmental hazards, etc. As a first step, this study aimed to provide an overview of biochar's properties, and operation by identifying the method of production and examining the differences between different types of biochar. Following that, by examining various factors that pollute the environment, the influence of different types of biochar on phytoremediation efficiency was explored. Also, in this study, an attempt has been made to examine the effect of the combination of biochar with other factors in improving the phytoremediation of pollutants, as well as the use of the residues of phytoremediation for the production of biochar, so that future research can be planned based on the results obtained.